2006
DOI: 10.1002/ajmg.b.30343
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme and angiotensin II type 1 receptor gene polymorphisms in children with subacute sclerosing panencephalitis

Abstract: Subacute sclerosing panencephalitis (SSPE) is a progressive, debilitating, and fatal brain disorder caused by mutant measles virus infection. Although both viral and host factors seem to be involved in SSPE, the exact pathogenesis remains to be determined. Autoimmune demyelination is characteristic of SSPE. The blood angiotensin-converting enzyme (ACE) activity and angiotensin II (Ang II) levels are associated with the ACE gene polymorphism. Proinflammatory effects of Ang II may contribute to the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In contrast, several recent reports have suggested that mutations in host interleukin-2, interleukin-4, interleukin-12, myxovirus resistance A, and angiotensin-converting enzyme genes are probably related to the onset of subacute sclerosing panencephalitis. [13][14][15][16] However, no data on gene mutation are available from Okinawa, and further research is needed to elucidate the mechanisms of onset.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several recent reports have suggested that mutations in host interleukin-2, interleukin-4, interleukin-12, myxovirus resistance A, and angiotensin-converting enzyme genes are probably related to the onset of subacute sclerosing panencephalitis. [13][14][15][16] However, no data on gene mutation are available from Okinawa, and further research is needed to elucidate the mechanisms of onset.…”
Section: Discussionmentioning
confidence: 99%
“…The association of host genes with immunity has been investigated. Several recent reports of polymorphisms in SSPE patients have suggested that the genes for interleukin-2 (IL-2), IL-4, IL-12, myxovirus resistance A, and angiotensin-converting enzyme are related to the onset of SSPE (23)(24)(25)(26). In particular, T-cell immunity is an important factor for the elimination of MV infection (1,27).…”
Section: Discussionmentioning
confidence: 99%
“…[26] Taşdemir et al demonstrated that the frequency of DD genotype and D allele was significantly higher in SSPE children. [27] Three candidate genes, MxA, IL-4 and IFN regulatory factor 1 genes, were studied in Japanese patients with SSPE. The TT genotype of MxA and CT genotype of IL-4 were found to relate SSPE susceptibility.…”
Section: Genetic Susceptibility Of Sspementioning
confidence: 99%